2021
DOI: 10.1186/s13640-021-00575-1
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue driving detection based on electrooculography: a review

Abstract: To accurately identify fatigued driving, establishing a monitoring system is one of the important guarantees of improving traffic safety and reducing traffic accidents. Among many research methods, electrooculogram signal (EOG) has unique advantages. This paper presents a systematic literature review of these technologies and summarizes a basic framework of fatigue driving monitoring system based on EOGs. Then we summarize the advantages and disadvantages of existing technologies. In addition, 80 primary refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 80 publications
0
8
0
Order By: Relevance
“…In studies using eye-tracking signals for fatigue detection, the main detection tools available are video signals, electrooculography signals, and multimodal fusion methods. The study of electrooculography (EOG) has been an important aspect of eye fatigue research [9][10][11][12]. The EOG signal is a measurement that uses electrodes placed in four directions: above, below, to the left, and to the right of the eye.…”
Section: Related Workmentioning
confidence: 99%
“…In studies using eye-tracking signals for fatigue detection, the main detection tools available are video signals, electrooculography signals, and multimodal fusion methods. The study of electrooculography (EOG) has been an important aspect of eye fatigue research [9][10][11][12]. The EOG signal is a measurement that uses electrodes placed in four directions: above, below, to the left, and to the right of the eye.…”
Section: Related Workmentioning
confidence: 99%
“…Further, adoption of reinforcement learning is reported in work of Langroodi and Nahvi [93] where fuzzy logic has been used together to prove its effectiveness over conventional artificial neural network (ANN) based approaches. Finally, the study carried out by Tian and Cao [94] have discussed about usage of electrooculography which is quite different from other approaches in order to determine fatigueness in driver. According to findings of this study, the aggregated approaches on electrooculography is found to be effective in contrast to other methods.…”
Section: Research Trendmentioning
confidence: 99%
“…Before video-based eye-tracking was widely available, electrooculography (EOG) was a technology psychologists used to track human eye movements (see [ 17 ], for a review). In addition to gaze information, the EOG signal also contains abundant information about the eyelid movements which can be used to derive measures sensitive to driver drowsiness, e.g., blinks or PERCLOS (for a recent review, see [ 18 ]). For instance, in a recent study by Xue et al [ 19 ], EOG electrodes were used to extract an eye closure measure, which was then used as a key parameter to assess driver fatigue.…”
Section: Related Workmentioning
confidence: 99%